2011
DOI: 10.1007/s12198-011-0073-4
|View full text |Cite
|
Sign up to set email alerts
|

On the success rates of maritime piracy attacks

Abstract: Today, modern pirates operate both in ports and on the open sea and use state-of-the-art equipment. Their crimes range from simple robbery to murder and hijacking of entire ships for ransom demand. It is the purpose of this paper to investigate the modern piracy trends and the effect of preventive actions taken by the crew of the attacked vessels. By analysing the available statistical material from the International Maritime Organization's (IMO) monthly piracy reports during the period 2000-2009, it is shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In terms of the organization of piracy, the more efficient is the pirate organization the greater is the probability of their not being caught on any given voyage, and, it can be supposed, the greater is the value of the booty captured (Leeson, ; Psarros et al ., ). Accordingly, modern‐day Somali pirates have developed supportive “social” organizations that aid them on land and at sea.…”
Section: Overview Of Piracy In Recent Timesmentioning
confidence: 97%
“…In terms of the organization of piracy, the more efficient is the pirate organization the greater is the probability of their not being caught on any given voyage, and, it can be supposed, the greater is the value of the booty captured (Leeson, ; Psarros et al ., ). Accordingly, modern‐day Somali pirates have developed supportive “social” organizations that aid them on land and at sea.…”
Section: Overview Of Piracy In Recent Timesmentioning
confidence: 97%
“…However, incidents in the Malacca Strait are rising and siphoning oil cargo from product tankerssimilar to incidents in the Gulf of Guineahas been reported also for this region. By analysing the available statistical material from the IMO's monthly piracy reports during the period 2000-2009, it is found that incidents off and around the African continent have led to fewer deaths as compared to those in South China Sea and Malacca strait (Psarros et al, 2011). This demonstrates that the attack rates on specific vessel segments and the recorded incidents for each geographical area develop their own trends.…”
Section: Maritime Piracy Patternsmentioning
confidence: 98%
“…Modern pirates use state-of-the-art equipment in their operations (Psarros et al, 2011). Their crimes range from simple robbery to murder and hijacking of entire ships for ransom demand.…”
Section: Maritime Piracy Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars (such as Psarros et al (2011)), organizations working with ship security (as described by such as Yang and Qu (2016) based on a formal safety assessment approach (IMO 2013)), and ship operators (as described by ; Liwång et al (2015)) perform security analyses. These types of analysis are needed to increase maritime security.…”
Section: Descriptive Modelsmentioning
confidence: 99%